Numerical simulation and experimentation of warm metal powder compaction process - Rahman M.M.; Tarlochan F.; Ramesh S.; Ariffin A.K.; Nor S.S.M. (Trans Tech Publications Ltd, 2023)
Powder compaction at elevated temperature or known as warm compaction is a process of producing green compacts from metal powder, which is generally conducted between the ambient and the recrystalization temperature of the main powder constituent. Even though, warm compaction was initiated at around 1998, not a lot of information can be found in the literature especially on the numerical simulation of the process. Therefore, this paper presents the simulation of warm metal powder forming process by using the developed computer code. The Elliptical Cap yield model has been used to represent the deformation behaviour of the powder mass during the forming process at above ambient temperature. The material properties of powder mass, i. e., friction coefficient, elastic index, and plastic index, at different forming temperature, are established through warm compaction experiment. The simulation was conducted to generate a green compact of a plain bush component. Some numerical simulation results were validated through experimentation, where a good agreement was found between the numerical simulation and the experimental results. (2011) Trans Tech Publications.